2006
DOI: 10.1007/s10709-006-7101-5
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionary chromosomal differentiation among four species of Conoderus Eschscholtz, 1829 (Coleoptera, Elateridae, Agrypninae, Conoderini) detected by standard staining, C-banding, silver nitrate impregnation, and CMA3/DA/DAPI staining

Abstract: The speciose Brazilian Elateridae fauna is characterized by high karyotypic diversity, including one species (Chalcolepidius zonatus Eschscholtz, 1829) with the lowest diploid number within any Coleoptera order. Cytogenetic analysis of Conoderus dimidiatus Germar, 1839, C. scalaris (Germar, 1824,) C. ternarius Germar, 1839, and C. stigmosus Germar, 1839 by standard and differential staining was performed with the aim of establishing mechanisms of karyotypic differentiation in these species. Conoderus dimidiatu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
24
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 27 publications
4
24
0
Order By: Relevance
“…This same pattern was also observed in the autosomal chromosomes of Coleoptera (Virkki, 1983, Schneider et al, 2006Mello et al, 2014). In the sex chromosomes, the heterochromatin can extend to all chromosome arms or is restricted exclusively in the pericentromeric region (Almeida et al, 2000;Rozek et al, 2004).…”
Section: Introductionsupporting
confidence: 70%
“…This same pattern was also observed in the autosomal chromosomes of Coleoptera (Virkki, 1983, Schneider et al, 2006Mello et al, 2014). In the sex chromosomes, the heterochromatin can extend to all chromosome arms or is restricted exclusively in the pericentromeric region (Almeida et al, 2000;Rozek et al, 2004).…”
Section: Introductionsupporting
confidence: 70%
“…The C-banding pattern observed in E. caribaeus is quite common among Scarabaeidae representatives and also to Coleoptera as a whole (Moura et al 2003;Colomba et al 2004Colomba et al , 2006Rozek et al 2004;Wilson and Angus 2004, 2005Bione et al 2005b;Schneider et al 2006). Meanwhile, particular cases of CH distribution have been reported in some Scarabaeidae; Cetonia aurata and Bubas bison have CH blocks located in the terminal region of eight autosomal bivalents, in addition to the pericentromeric blocks (Colomba et al 1996(Colomba et al , 2006Dutrillaux et al 2006).…”
Section: Discussionmentioning
confidence: 99%
“…In Coleoptera, examples of diploid number reduction and/or neo-XY origin were observed in Elateridae, Conoderus stigmosus (2n = 16, neo-XY), Lampyridae, Bicellonycha lividipennis (2n = 18, neo-XY) and other families (Schneider et al 2006;Dias et al 2007). This pattern of chromosomal evolution in insects has also been seen in other orders, for e.g., Heteroptera (Bressa et al 1999), Odonata (Mola and Papeschi 1994), and to arthropods in general in spiders (Rezac et al 2006) and pseudoscorpions (Stahlavsky and Kral 2004).…”
Section: Discussionmentioning
confidence: 99%
“…However, numeric and morphologic variation in chromosomes of different taxa, for example, in families and subfamilies, have been described in the literature. Different structural rearrangements such as Robertsonian rearrangements and in tandem fusions and fissions can be responsible for such variations (Smith and Virkki, 1978;Vidal and Nocera, 1984;Petitpierre et al, 1991;Schneider et al, 2006;Moura et al, 2008;Cabral-de-Mello et al, 2008). The 2 species described herein differed with regard to the diploid number, chromosomal morphology, and sex chromosome bivalent.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the origin of the neoXY system in the tenebrionid Pimelia sparsa sparsa (8 + neoXY) has been thought to result from a rearrangement involving the ancient Xyp with loss of most of the existent heterochromatin in the X chromosome (Pons, 2004). Schneider et al (2006) also suggested that the fusion of autosomal/Xy chromosome might be responsible for the origin of the 7 + neoXY karyotype in Conoderus stigmosus (Elateridae).…”
Section: Discussionmentioning
confidence: 99%